2014
DOI: 10.4028/www.scientific.net/msf.775-776.498
|View full text |Cite
|
Sign up to set email alerts
|

Study of Morphology Membrane of Polymeric Nanocomposites Obtained by Phases Inversion

Abstract: In this work, were obtained nanocomposite membranes polyamide66/Paraíba bentonite clay, treated with a quaternary ammonium salt in order to make it organophilic. The membranes were prepared as thin films using the technique of phase inversion from the nanocomposites obtained by solution. The membranes were characterized by X-ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetry (TG) and scanning electron microscopy (SEM). By means of X-ray diffractogram, it was revealed that the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
6
0
4
Order By: Relevance
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…Polyamides are semicrystalline polymers and the presence of peak broadening indicates the existence of amorphous regions. Furthermore, the introduction of clay, regardless of the amount, changes slightly the shape and intensity of the peaks at 20º and 24º of the polyamide6 [30][31][32][33][34][35] . It was found that the addition of 5% w/w of MMT in PA6, cause the appearance of the new reflection at 2θ = From Figure 2, it is noted that the general profile of FTIR spectra of the PA6 remained virtually unchanged, except for a small increase in the intensity of the peaks at wavelengths of 800, 1033 and 1095 cm -1 .…”
Section: Water Permeability and Oil Retentionmentioning
confidence: 99%
“…A poliamida 6 é um polímero semicristalino e o alargamento dos picos indica a existência de regiões amorfas. Como pode ser observada, a introdução da argila, independente do percentual, altera um pouco o formato e a intensidade dos picos característicos da cristalinidade da poliamida 6 na faixa de aproximadamente 20º e 24º [23,24].…”
Section: Figuraunclassified
“…A diferença da morfologia entre o tamanho de poros apresentado pela camada superficial em relação à camada porosa é que caracteriza a seletividade das membranas [32]. Pode-se verificar que a membrana de PA6 pura (Figura 4) apresentou uma superfície de topo com poros muito pequenos e uma baixa interconectividade destes com os poros da seção transversal, além disso, ao longo de sua espessura foi possível observar poros esféricos na camada porosa [23,24].…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Recently, various types of clay, such as montmorillonite, have been used as reinforcement in the production of polymer nanocomposites and promising results for applications of polyamide nanocomposite in membranes have been published . The objective of this research was to evaluate the microstructure and the porosity of the polyamide 6 polymer and hybrid membranes for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%